Efektivitas Konsumsi Ikan Lele Sebagai Alternatif Pemberian Makanan Tambahan (PMT) Untuk Anak di Bawah Usia 3 Tahun - hardiana, Yunita; Nugraeni, Dyan Kunthi; Riyanto, Agus; Budiman, Budiman (Poltekkes Kemenkes Semarang, 2024)
Background: One of the health problems that often occurs in children under 3 years of age is underweight. The prevalence of underweight in Purwakarta Regency is 14.1%. One of the efforts to overcome this underweight problem is through the Supplementary Feeding Programme (PMT). Catfish can be an option of food ingredients for PMT because it is high in protein and omega-3. Objective: To determine the effectiveness of catfish consumption as an alternative to supplementary feeding (PMT) for children under 3 years of age.Methods: This research design used a quasi-experiment with a non-equivalent control-group before-after design approach. The sample size was 30 children for each intervention and control group. Statistical analysis used univariate, bivariate using paired T-test and Independent T-test, effectiveness using N-Gain test, and multivariate multiple logistic regression test. Results: The results of the study using a paired T-test showed that there was a difference in the increase in body weight before and after administration of catfish PMT in the intervention and control groups (p-value = 0.001). The independent t-test results showed no significant difference in body weight after administration of catfish PMT in the intervention and control groups (p-value = 0.182). The results of the N-Gain test showed that the intervention group had an average of 7.55% and the control group had an average of 6.99%, which means that the provision of catfish PMT on weight gain is ineffective in the intervention and control groups.